Classification of Coronary Heart Disease at Semen Padang Hospital using Algorithm Classification And Regression Trees (CART) - defal aditya defran; Atus Amadi Putra; Dodi Vionanda; Tessy Octavia Mukhti (Departemen Statistika Universitas Negeri Padang, 2023)
Cardiovascular disease is a degenerative disease caused by decreased function of the heart and blood vessels. One of the heart diseases that is very popular today is coronary heart disease (CHD). The main factors that cause CHD include age, gender, hypertension, blood sugar and cholesterol. One method that can be used to group CHD is classification. Classification And Regression Trees (CART )is a decision tree that describes the relationship between a response variable and one or more predictor variables. The goal of CART is to obtain an accurate data group as a characteristic of a classification. Based on the results of the optimal tree, the attribute that is the main characteristic in classifying CHD patients at Semen Padang Hospital is age. The determination of the classification results using the confusion matrix produced an accuracy value of 66.67%, a sensitivity of 56.52% for classifying CHD patients, and a specificity of 84.61% for classifying non-CHD patients.